Knowledge audit portal for higher learning institution - Alias, Rose Alinda; Sulaiman, Nor Intan Saniah (2004)
Knowledge Audit is one of the activities that should be conducted prior to development of a Knowledge Management System in an organization. Knowledge audit facilitates identification of the various forms of knowledge that are required by stakeholders of a Knowledge Management System. However, despite its importance, few KMS developers perform knowledge audit.Thus, the main objective of this study is to develop a portal prototype that serves as a KMS as well as a knowledge auditor.The portal is developed specifically for academic staff and students in a public institute of higher learning.This study is initiated with a questionnaire that is used to identify explicit knowledge required by an academic community.The responses are used to develop the prototype Knowledge Audit Portal.This prototype was designed using Rational Rose 2000, Macromedia Dreamweaver MX(for interface development) and Active Server Pages (ASP) technology(used for prototype coding).The portal demonstrates how knowledge required by a community of academic staff and student can be identified as the community uses a basic portal.